Os cem olhos do pavão - Marcelo Amato Cardoso (Medievalista)
The peacock is considered one of the most beautiful animals in nature. This beauty, concerning the imaginary, becomes a key element in the narratives and arts that associate the peacock with the Hindu and Buddhist deities, but also with the pride and the vanity. This article tries to show how the symbolism of the peacock was transmitted and adapted from Ancient India to Medieval Europe, where the bird figured in the Christian creativity as an emblem of the immortality of Christ and the preachers of the Church, along with hagiographical narratives and biblical images.